Validity and reliability of the multidimensional student's life satisfaction scale among Iranian girl students - Mojtaba Habibi; Minoo Pooravari; Somaieh Salehi; Zahra Ghamkhar Fard; Marjan Pooravari (Gonabad University of Medical Sciences, 2015)
Life satisfaction is a subjective and unique concept for each person that constitutes an essential component of the subjective well-being. The aim of his study was investigating the psychometric properties of Multidimentional student's Life Satisfaction Scale (MSLSS) by using confirmatory factor analysis. Sample size of 307 students in Tehran were selected randomly. To calculate the convergent validity of MSLSS, Satisfaction with Life Scale and Body Image Concern Inventory were implemented. Confirmatory factor structure for the first-order approach to MSLSS estimated using weighted least squares (WLS) criteria for assessing the adequacy of the data model with RMR, RMSEA, CFI, AGFI, GFI, 2c, / df2 c and 2 D c used. Cronbach's alpha coefficient of MSLSS was above 0.70 and the limit was satisfactory. Factor structure of the MSLSS after the first time using confirmatory factor analysis was confirmed. Correlation coefficient analysis showed that MSLSS is a significant positive relationship with Satisfaction with Life Scale and significant negative relationship with Body Image Concern Inventory which shows the convergent validity. A single first-order factor structure of MSLSS were better fit with the observed data. Confirmatory factor structure, reliability and validity of the MSLSS for research applications and clinical diagnostics were within acceptable limits